2008
DOI: 10.1080/02602930701562874
|View full text |Cite
|
Sign up to set email alerts
|

Assessing test‐taking strategies of university students: developing a scale and estimating its psychometric indices

Abstract: Test-taking strategies are important cognitive skills that strongly affect students' performance in tests. Using appropriate test-taking strategies improves students' achievement and grades, improves students' attitudes toward tests and reduces test anxiety. This results in improving test accuracy and validity. This study aimed at developing a scale to assess students' test-taking strategies at university level. The scale developed was passed through several validation procedures that included content, constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 17 publications
0
33
0
4
Order By: Relevance
“…For example, to use elimination processes or look for clues in the item stem when guessing, or if no clues are to be found to make an educated or intelligent guess. Using these types of guessing strategies might lead to better results regardless of ability level and better results than other students at the same ability level not using these types of strategies (Dodeen 2008). It has been found that the willingness to 404 Stenlund T. et al guess (i.e., risk-taking) has increased over the years, and that changed test-taking behaviors, such as to use guessing and effective elimination processes to increase the odds of choosing a correct answer, even might be a reasonable explanation to the secular gain in measured IQ over time, that is the so-called Flynn effect (Woodley et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, to use elimination processes or look for clues in the item stem when guessing, or if no clues are to be found to make an educated or intelligent guess. Using these types of guessing strategies might lead to better results regardless of ability level and better results than other students at the same ability level not using these types of strategies (Dodeen 2008). It has been found that the willingness to 404 Stenlund T. et al guess (i.e., risk-taking) has increased over the years, and that changed test-taking behaviors, such as to use guessing and effective elimination processes to increase the odds of choosing a correct answer, even might be a reasonable explanation to the secular gain in measured IQ over time, that is the so-called Flynn effect (Woodley et al 2014).…”
mentioning
confidence: 99%
“…Informing prospective test takers about these insights can potentially lead to more valid interpretations and inferences based on the test scores. Eur J Psychol Educ (2018) shown that for a test taker to be successful when taking a test, it is important to be able to reduce anxiety and sustain motivation (Dodeen et al 2014;Naylor 1997;Sternberg 1998), as well as using effective test-taking strategies, such as willingness to take risks (Bicak 2013;Bond and Harman 1994;Dodeen 2008). Studies in this area often compare groups of test takers and have for example found that high achievers tend to report using more effective testtaking strategies when compared to low achievers (Stenlund et al 2017;Ellis and Ryan 2003;Hong et al 2006;Kim and Goetz 1993), that males are more prone to taking risks when answering test items (see, e.g., Baldiga 2014), and that females and low achievers seem to experience higher levels of test anxiety than males and high achievers (Stenlund et al 2017;Cassady and Johnson 2002;Naylor 1997).…”
mentioning
confidence: 99%
“…This instrument was selected because it has already been applied in at least two studies (Dodeen, 2008;Dodeen, Abdelfattah, & Alshumrani, 2014) measuring learners' attitudes. Despite its use in studies related with mathematics, it also has application across the disciplines.…”
Section: Instrumentsmentioning
confidence: 99%
“…In order to measure learners' attitudes regarding tests, both the control and the experimental group answered the Attitude towards Test Scale (ATS) (Dodeen, 2008) (see Appendix A) prior to the instructional period and at its conclusion. This survey consists of 17 questions that are answered using a Likert scale from "Strongly Disagree" to "Strongly Agree".…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation